FACTORS INFLUENCING ENTREPRENEURIAL INTENTION TO CULINARY MSMEs IN JAKARTA - Kania, Yanti; Handoyo, Sarwo Edy (International Journal of Application on Economics and Business, 2024)
The purpose of this study was to determine 1) the effect of self-skill awareness on entrepreneurial intention 2) the effect of entrepreneurial resources on entrepreneurial intention, 3) the effect of entrepreneurial networks on entrepreneurial intentions, 4) the effect of entrepreneurial self-efficacy on entrepreneurial intentions, 5) the effect of self-efficacy entrepreneurship as mediation of entrepreneurial networks on entrepreneurial intentions. The sample selection technique used in this study was non-probability sampling and the sampling technique used purposive sampling technique. Data was taken using an online google form questionnaire with a total of 100 respondents. in this study using 4 indicators on each variable. Processing of research data using SmartPLS 4.8. The sample in this study are culinary MSME owners in Jakarta. The results of this study are 1) self-skill awareness does not affect entrepreneurial intentions. 2) entrepreneurial resources do not affect entrepreneurial self-efficacy 3) entrepreneurial networks affect entrepreneurial intentions. 4) entrepreneurial self-efficacy affects entrepreneurial intentions 5) entrepreneurial self-efficacy can mediate the effect of entrepreneurial resources on entrepreneurial intentions 6) entrepreneurial networks can influence entrepreneurial intentions through mediating entrepreneurial self-efficacy.